2019
DOI: 10.3390/su11020436
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Transformational Leadership on Job Performance and CSR as Mediator in SMEs

Abstract: Leadership style is an important factor that affects the enhancement of organizational performance and employee’s job performance, and what objectives they should pursue, which also makes a profit for their employees or makes another social and economic contribution to society. The present study was developed to observe the impact of transformational leadership on job performance and to investigate the mediating mechanism of corporate social responsibility (CSR). Primary data were collected from the employees … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
135
1
23

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 168 publications
(168 citation statements)
references
References 47 publications
9
135
1
23
Order By: Relevance
“…When these motivated employees show creative behavior with their work, they receive appreciation and respect from their leaders, team members, and even from the customers in return [18]. Consequently, they possess auspicious behavior connected with their jobs, which allows them to become extra passionate and productive [63,64].…”
Section: The Mediating Role Of Affective Commitment and Work Engagementmentioning
confidence: 99%
“…When these motivated employees show creative behavior with their work, they receive appreciation and respect from their leaders, team members, and even from the customers in return [18]. Consequently, they possess auspicious behavior connected with their jobs, which allows them to become extra passionate and productive [63,64].…”
Section: The Mediating Role Of Affective Commitment and Work Engagementmentioning
confidence: 99%
“…A Cronbach's alpha reliability range above 70% for each variable indicates that the collected data is reliable [70]. Hair et al [71] recommended that given data would be considered reliable if the alpha value was greater than 60 percent [72]. In Table 2, the results of the Cronbach's alpha showed that inclusive data is observed within a given reliability range.…”
Section: Reliability Analysismentioning
confidence: 99%
“…Bukti-bukti empiris menemukan bahwa gaya kepemimpinan transformasional berhubungan positif dengan prestasi kerja, yaitu: (B. Lowe, Kroeck, & Sivasubramaniam, 1996;Barling, Weber, & Kelloway, 1996;Chi & Pan, 2012;Dvir, Eden, Avolio, & Shamir, 2002;Ekaningsih, 2014;Kirkpatrick & Locke, 1996;Mangkunegara & Miftahuddin, 2016;Manzoor et al, 2019). Carmeli & Freund (2004), menjelaskan bahwa komitmen organisasional berpengaruh positif terhadap prestasi kerja karyawan.…”
Section: Kajian Literaturunclassified